2020
DOI: 10.1101/2020.09.07.284612
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dopamine D2 receptors modulate the cholinergic pause and inhibitory learning

Abstract: Cholinergic interneurons (CINs) in the striatum respond to salient stimuli with a multiphasic response, including a pause, in neuronal activity. Slice physiology experiments have shown the importance of dopamine D2 receptors (D2Rs) in regulating CIN pausing yet the behavioral significance of the CIN pause and its regulation by dopamine in vivo is still unclear. Here, we show that D2R upregulation in CINs of the nucleus accumbens (NAc) lengthens the pause in CIN activity ex vivo and enlarges a stimulus-evoked d… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 75 publications
1
9
0
Order By: Relevance
“…This is particularly important considering that tonically-active CINs also co-release glutamate, and in vivo electrophysiological methods cannot distinguish the consequences of ACh and glutamate release. Consistent with a previous report using a Go/No-Go task in mice 102 , we observed that NAc ACh dynamics in control mice performing the Autoshaping task are mainly characterised by a transient reward-evoked decrease in cholinergic tone, likely reflecting the pause of activity of CINs electrophysiologically detected in vivo. This profound decrease of cholinergic signals correlates with the acquisition of approach behaviours, suggesting a relevant gating mechanism necessary for the acquisition or maintenance of cue-motivated learning behaviours.…”
Section: Discussionsupporting
confidence: 92%
“…This is particularly important considering that tonically-active CINs also co-release glutamate, and in vivo electrophysiological methods cannot distinguish the consequences of ACh and glutamate release. Consistent with a previous report using a Go/No-Go task in mice 102 , we observed that NAc ACh dynamics in control mice performing the Autoshaping task are mainly characterised by a transient reward-evoked decrease in cholinergic tone, likely reflecting the pause of activity of CINs electrophysiologically detected in vivo. This profound decrease of cholinergic signals correlates with the acquisition of approach behaviours, suggesting a relevant gating mechanism necessary for the acquisition or maintenance of cue-motivated learning behaviours.…”
Section: Discussionsupporting
confidence: 92%
“…In Table 1 you will find a summary of currently available DA biosensors as well as their main properties, which are further detailed in Section 5 . DA biosensors have already generated key findings in the basic understanding of reward behavior [ 101 , 102 , 103 , 104 , 105 , 106 , 107 ], thirst regulation [ 108 ], feeding behavior [ 109 ], addiction [ 38 , 110 , 111 ], aversive learning [ 112 ], depressive-like behavior [ 98 ], sleep-wake cycle [ 113 ] or to dissect neuromodulator mechanisms in disease models [ 114 , 115 ] using a variety of in vivo imaging modalities shown in Figure 1 . DA biosensors can also be used to understand DA release dynamics in vitro or ex vivo [ 58 , 59 , 60 , 61 ], as shown for example in Reference [ 116 ] where dLight1 was used to understand the metabolic demands and bioenergetic roles of the mitochondria in governing phasic DA release.…”
Section: Catalogue Of Gpcr Biosensors For Dopaminementioning
confidence: 99%
“…Next, among the sensors selected, it is best to favor a sensor with maximal dynamic range (if possible, >250–300%). We found that dLight1.1, dLight1.2 and RdLight1 displayed an optimal combination of medium ligand affinity (330 nM, 765 nM and 860 nM, respectively) and good dynamic range (230%, 340% and 250%, respectively), making them ideally suited for in vivo bulk (photometry) imaging of large DA transients in response to rewards or cues in the heavily innervated striatum or NAc [ 58 , 59 ], see also: [ 107 , 110 , 111 , 112 , 113 , 115 , 224 , 225 ]. On the other hand, sensors with high and extremely high affinity such as GRAB-DA2m (K d = 90 nM; dFFmax = 340%; validated in vivo), GRAB-DA2h (K d = 7 nM; dFFmax = 280%; validated in vivo) [ 61 ] and dLight1.4 (K d = 4.1 nM; dFFmax = 170%; not validated in vivo yet) [ 58 ]; as well as other sensors in development (not shown) are ideally suited to detect DA release in brain regions with sparser and extremely sparse innervation or may potentially be used to track tonic DA changes in the nanomolar range [ 11 ] (this remains to be determined).…”
Section: Practical Considerations For Sensor Choice: One Sensor Domentioning
confidence: 99%
See 1 more Smart Citation
“…First, CINs influence striatal output by modulating cortico-striatal plasticity in SPNs [26,27], which are thought to play key roles in action selection and reward valuation [28,29]. Second, CINs not only powerfully control local dopamine release [30][31][32], but their cue-evoked firing activity and acetylcholine release is, in turn, sensitive to dopamine actions on D2Rs [33][34][35]. Third, recent work involving systemic administration of cholinergic receptor agonists and antagonists has suggested a complex involvement of acetylcholine in delay and probabilistic discounting tasks [36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%